PERUBAHAN PERSEPSI MELALUI PELIBATAN MASYARAKAT DALAM PROSES ANALISIS MENGENAI DAMPAK LINGKUNGAN (AMDAL) PLTGU PERAK - Endang Susilowati; Sukriyah Kustanti Moerad (JURNAL SOSIAL HUMANIORA (JSH), 2016)
The residential area and industrial economy in Indonesia specifically East Java has grown rapidly. This is a challenge for National Electricity Board such as P.T. PLN Persero East Java to supply the energysufficiently. Therefore P.T.PLN Persero through the branch company, P.T.Indonesia Power will build four (4) new plants with huge capacity more than 1,000 MW. One of the plant will be built in the administrative area of Perak Utara Village, Pabeaan Cantikan District-Surabaya City. The plant will be generated with gas and steam (PLTGU), that is a combined cycle between the electricity plant which is powered with gas (PLTG) and the electricity which is powered with steam (PLTU). The development of PLTGU is aimed for many benefits, such as: to fulfill electricity that has continually increased; to improve domestic, business or industry activities through continually electricity supply; as the peak loader of Java-Bali electricity supply system; and it is also aimed for supporting the 35,000 MW electricity government program. Even though there are many benefits of the development, it is often facing many problems in its implementation from community affected project around study area because of their negative perceptions. So it is important to conduct a community approach through project socialization and public consultation meeting (PKM) for gaining perception change, from negative to positive perception toward development activities.